PRINCIPLE OF THE BALANCE OF INTERESTS; NORMATIVE AND APPLICATIVE EPISTEMOLOGICAL APPROACHES IN THE COSTA RICAN LEGAL SYSTEM - Sánchez Sánchez, Juan Diego (2023)
The paper addresses the main conceptual bases referring to the principle of the Interests Equilibrium, as well as its normative and legal approaches to its development within the Costa Rican legal system, specifying at the same time its considerations and practical applications in jurisprudential matters. An analysis of the relevant doctrine is used to support the elements of the inherent balance that must prevail in contracts, which although has a main focus on Public Law and contracts generated between a contractor and the State, it can also be extrapolated to contractual matters in general,  pointing out as aspects of relevance issues such as the public purpose of the agreement, the reasonable profit of the contractor, contractual modifications, and the balance as to the equal importance of the interests of the parties to the contract on which the principle of the Balance of Interests must be respected.